KEBIJAKAN MORATORIUM DAN PENATAAN PEGAWAI NEGERI SIPIL BAGIAN DARI REFORMASI BIROKRASI - Ajib Rakhmawanto (Jurnal Manajemen Kepegawaian, 2011)
One of the goalsof bureaucratic reformis to achieve good governance. As advanced, needs to be done a variety ofchanges to administrative systems, such aspolitical system, the clarity of the functions of government agencies aswell ashuman resource management of civil servants. Moratorium policy is issued because of uneven distribution ofcivil servants, both in terms ofquantity and quality, in addition to saving state finances. Cumulation of employees insome government institutions and the unequal distribution of employees are the reasons that has caused bureaucracyperformance become sluggish and ineffective, so that the structuring/rightsizing of civil servants is required. It is expectedthat by rationally structuring employee, there will be harmony between the organization and composition of civil servantsin all government institutions.Key woods: moratorium, structuring employee, bureaucratic reform